Sistemas de Recomendação para percursos culturais - Francisca Reis Rodrigues (2019)
Being an institution of memory, with a vast information, the museum of the University of Porto is a place of high importance that must be taken care of. The trasmission, sharing and dissemination of this information to all the public to which it available, should be facilitated.The #IWASHERE application createad by the museum intends to meet this difussion of information. The application relies on the identification of Points of Interest and digital scripts referring to the city of Porto. With the large target audience and with undeniable advantages, this is essential to create a Recommendation System to facilitate user search.The goal is to organize all the tools that allow a recommendation of a new route or new Points of interest to a user in the system. For this, two different scenarios are presented, both using collaborative filtering. The first makes the similarity between paths and the second makes the similarity between points. Defining the optimization problema will allow to recommend new routes using the points visited by users that the active user has not yet visited.